Draw Your Own Game: Design Games with the RULER.game Collaborative Computational Thinking Tool (Constructionism Conference Proceedings, 2025)
Imagine your students creating sophisticated games by combining hand-drawn art with AI – all while reducing their screen time. This workshop introduces RULER.game, where even programming novices such as first graders can build Pac-Man-like games with collaborating ghosts, bridging the gap between physical creativity and digital innovation. This workshop introduces Collaborative Computational Thinking Tools (CCTTs) through RULER.game, which combines off-screen activities like drawing game assets on paper with collaborative learning and AI-enabled programming. Participants will create a Pac-Man-like game and understand the distinction between contemporary block-based programming and CCTTs. The workshop examines how CCTTs address semantic and pragmatic programming concerns through prebugging, while Proxy-Based Programming blends block-based programming with programming by example to overcome semantic challenges. RULER.game is free, enabling students to create and play sophisticated games through collaborative creation and gameplay by combining hand-drawn assets with AI functions. Games can be programmed with RULER.game on tablets, laptops, smartphones and in VR environments.